Software para o processo de enfermagem no serviço de atendimento móvel de urgência fundamentado nas necessidades humanas básicas - Silva, Hudson Soares da (2023)
Introduction: Software is an information transforming product, considered the most relevant today and one of the most important technologies in the global context. Objective: The present study aimed to produce and validate software for the nursing process in the Mobile Emergency Care Service (SAMU), based on Basic Human Needs (NHB). Methodology: This is a mixed intervention study, developed in three stages that took place sequentially and sometimes concomitantly, the first stage being the Software Specification, the second its Design and Implementation, the third the Software Validation. To this end, documentary sources were used through the analysis of SAMU records, and oral sources through the focus group technique. Results: Document analysis made it possible to adapt the technology to the most recurrent situations in the service and critically describe the nursing team's way of providing care. The production of the software counted on the partnership of the service's nursing managers, in addition to hiring a Computer Engineering company to provide the necessary technical support, this allowed the construction of functional software with Software Quality Assurance, for use in the System. Android, and this makes the dissertation and the product unique. Regarding the evaluation of study participants, the presentation, content and usability criteria were met, in addition to the fundamental characteristics of simplicity, ubiquity, flexibility, personalization and localization. Conclusion: It is concluded that the proposed objective of producing and validating the software for the Nursing Process in the SAMU based on the NHB was met, suitable for the functioning of the institution and with the characteristics inherent to the current reality of the Metropolitan SAMU in the city of Salvador.